Optimal Design of Barangay Rogongon Microgrid System: Optimal Design of Barangay Rogongon Microgrid System - Tahud, Anacita Palma; Estoperez, Samuelle Jane Dahili; Wayco, Jeryl Manlupig; Estoperez, Noel Regis (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this research, specifically an electrical distribution system design of the proposed microgrid in a remote barangay, Brgy. Rogongon, in Iligan City, is presented. Due to limited access and limited-service electrical utility grid, about 10 % of the Philippine household population at a development disadvantage. Through the project, potential sites for hydropower and solar PV installations as well as distribution pathways were identified using Geographic Information (GIS). Household surveys were conducted to obtain the 5 yr projected load demand and the results are presented in thematic maps. The electrical distribution system of the microgrid was designed and simulated using Just Another Electrical Distribution Network Software (JAED.NS). The system simulation showed an acceptable 5.94 % estimated total system loss which implies that the designed electrical distribution system is feasible.